A case of bronchogenic cyst of the diaphragm misdiagnosed as pulmonary cyst - Liu Qihe, Yang Yan, Wen Qianqian, Cai Qingyong (Xin yixue, 2022)
Bronchogenic cyst is a congenital disease, which is rarely derived from the diaphragm. In this article, one case of bronchogenic cyst of the diaphragm misdiagnosed as pulmonary cyst was reported. A 46-year-old female patient was admitted to our hospital due to intrathoracic mass detected by chest CT. Combined with MRI results, she was diagnosed with the right lower pulmonary cyst before operation. After eliminating surgical contraindications, the cyst was removed under thoracoscope. Intraoperatively, it was found that the cyst originated from the diaphragm, which had a clear boundary with the right lower lung tissues. The diagnosis of bronchogenic cyst of the diaphragm was confirmed by pathological examination. Physical conditions of the patient were stable during postoperative 6-month follow-up.